PsycTESTS Dataset 2014
DOI: 10.1037/t55295-000
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Expectativa de los Hijos Adolescentes sobre la Reacción de sus Padres

Abstract: r e s u M e n El objetivo de esta investigación es presentar una adaptación y validación en población española de la Escala de Expectativa de los hijos adolescentes sobre la reacción de sus padres frente al comportamiento prosocial y antisocial, desarrollada por Wyatt y Carlo (2002). La muestra estuvo compuesta por 631 adolescentes españoles de entre 15 a 18 años de edad, de clase media, de ambos sexos. Se realizó un análisis factorial confirmatorio para estudiar la validez de constructo de la escala y se anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The scientific literature on the relationship between aggressive behavior towards peers at school and variables of psychological adjustment has focused mainly on identifying risk factors that predispose or precipitate an intimidating and humiliating behavior toward other classmates [10]. In particular, among the risk factors identified in the adolescent stage for the development of aggressive behavior towards peers are, among others: low life satisfaction [11,12], high psychological distress [13], deficits in empathic ability [14,15], tendency to depressive symptomatology [16], and low self-esteem [17]. Taylor et al [18] observed that aggressors have a positive self-concept in the physical (physical attractiveness) and social dimensions (popularity), but they report more negative self-perceptions in reference to the family and academic domains of self-concept.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature on the relationship between aggressive behavior towards peers at school and variables of psychological adjustment has focused mainly on identifying risk factors that predispose or precipitate an intimidating and humiliating behavior toward other classmates [10]. In particular, among the risk factors identified in the adolescent stage for the development of aggressive behavior towards peers are, among others: low life satisfaction [11,12], high psychological distress [13], deficits in empathic ability [14,15], tendency to depressive symptomatology [16], and low self-esteem [17]. Taylor et al [18] observed that aggressors have a positive self-concept in the physical (physical attractiveness) and social dimensions (popularity), but they report more negative self-perceptions in reference to the family and academic domains of self-concept.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 731 participants completed this questionnaire. Validated versions of this test were available in all the languages used in our survey (French [45], Spanish [46], Italian [47], Portuguese [48], German [49], Dutch [50] and Hebrew [51]).…”
Section: Methodsmentioning
confidence: 99%
“…), few negative social behaviours (aggressive or antisocial behaviours, etc. ), a high level of self-concept, numerous assertive interaction strategies, a significant ability to analyse negative emotions and strong emotional stability (Mestre Escrivá, Frías Navarro, & Samper García, 2004). Likewise, certain pedagogical interventions have been shown to be effective in increasing empathy and therefore boosting altruistic prosocial behaviour (Etxeberría et al, 1994; Mestre Escrivá et al, 1999; Vettorazzi et al, 2005).…”
Section: Contents Of Political Socializationmentioning
confidence: 99%
“…A su vez, en este proceso juega un rol fundamental el nivel de desarrollo cognitivo de los individuos, el cual posibilitará valorar los hechos a los que se enfrenta pudiendo ir más allá de lo concreto de la situación (Mestre Escrivá, Pérez Delgado, & Samper García, 1999). Estudios con niños/as señalan que aquellos/as niños/as que muestran una alta empatía evidencian muchas conductas sociales positivas de distinto tipo (liderazgo, prosociales, consideración, entre otras), pocas conductas sociales negativas (agresivas, antisociales, entre otras), un nivel alto de autoconcepto, numerosas estrategias de interacción asertivas, una gran capacidad para analizar emociones negativas y una alta estabilidad emocional (Mestre Escrivá, Frías Navarro, & Samper García, 2004). Asimismo, ciertas intervenciones pedagógicas han mostrado su efectividad para aumentar la empatía y por lo tanto incrementan la conducta prosocial altruista (Etxeberría et al, 1994; Mestre Escrivá et al, 1999; Vettorazzi et al, 2005).…”
Section: Contenidos De La Socialización Políticaunclassified